Water-based efficient and stable CsPbI3 quantum dot optical thin film and low-temperature preparation method thereof
By utilizing the interaction between polymer PVA and perovskite in an aqueous solvent system, CsPbI3@PVA is synthesized under low temperature conditions, and the problem of unstable CsPbI3 quantum dot optical film in the prior art is solved, achieving efficient and stable red light emission effect.
Patent Information
- Application Number
- CN202411701209.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-04-04
AI Technical Summary
The prior art is difficult to synthesize a stable red light-emitting CsPbI3 quantum dot optical film under low temperature conditions, and it is prone to phase change, resulting in unstable luminous performance.
In an aqueous solvent system, CsPbI3@PVA is synthesized under low temperature conditions by using the interaction between polymer PVA and perovskites, and an efficient and stable red light emitting film is formed through ultrasonic, scraping, heating film formation and humidity treatment.
The efficient and stable red-light-emitting CsPbI3 quantum dot optical film is achieved under low temperature conditions, with good photoluminescence efficiency, thermal stability and anti-blue light stability.
Smart Images

Figure CN119752443A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of luminescent materials and relates to a water-based highly efficient and stable CsPbI3 quantum dot optical film and a low-temperature preparation method thereof. Background Art
[0002] Perovskite nanocrystals have attracted extensive attention due to their excellent optoelectronic properties such as high color purity, tunable narrow-band emission and low cost. In particular, the development of APbX3 (A = Cs, MA, FA; X = Cl, Br, I) color conversion films has made significant progress and is believed to be able to change the field of high-definition display technology. At present, green-emitting MAPbBr3 color conversion films have been commercialized and successfully applied to the display field. However, red-emitting CsPbI3 is extremely prone to negative phase transitions due to its thermodynamic instability caused by low Schmidt tolerance factor and the high activity characteristics of iodine ions, that is, it is easy to change from the luminescent black phase to the non-luminescent yellow phase under the temperature and humidity of the environment. Therefore, the preparation of phase-stable red-emitting CsPbI3 is a barrier that must be overcome for application in color conversion films. In addition, the synthesis of stable red-emitting CsPbI3 requires overcoming a high energy barrier, and high-temperature heating of more than 130°C is usually required during the preparation process, which increases the cost, risk and complexity of the manufacturing process. Therefore, it is crucial to develop a low-temperature preparation method for highly stable CsPbI3 composite films.
[0003] The main challenge in synthesizing stable red-emitting CsPbI3 at low temperature is to minimize the formation of the non-luminescent yellow phase and prevent its transition from the red-emitting black phase to the yellow phase. When the synthesis temperature is lowered, the inherent instability of CsPbI3 will not only promote the generation of the yellow phase, but also cause the already generated luminescent perovskite to convert to the non-luminescent phase, making it a greater challenge to achieve stable red emission under low temperature conditions.
[0004] In addition, in order to effectively control the nucleation and growth kinetics of the precursors, the choice of solvent during the preparation process is a key. The formation of perovskite nanocrystals in a polymer matrix requires the synchronous precipitation of different precursors, which can usually be achieved by manipulating temperature or gas pressure. Commonly used solvents, such as N,N-dimethylformamide (DMF), dimethyl sulfoxide (DMSO), and γ-butyrolactone (GBL), all have relatively high boiling points of 153°C, 189°C, and 204°C. These high boiling points may result in too low evaporation rates at low temperatures, leading to incomplete precursor conversion and significant agglomeration. Therefore, choosing a suitable solvent is crucial for successful low-temperature synthesis. Summary of the invention
[0005] The purpose of the present invention is to address the above-mentioned problems existing in the prior art and to propose a method for synthesizing CsPbI3@PVA under low temperature conditions in an aqueous solvent system by utilizing the interaction between polymer and perovskite, and to produce an aqueous-based high-efficiency and stable CsPbI3 quantum dot optical film with good photoluminescence efficiency, thermal stability and anti-blue light stability.
[0006] The purpose of the present invention can be achieved by the following technical solutions:
[0007] A water-based, highly efficient and stable CsPbI3 quantum dot optical film is prepared by adding CsI and PbI2 into a PVA aqueous solution to obtain a precursor solution, and the precursor solution is subjected to ultrasound, scraping, heating film formation and humidity treatment.
[0008] Preferably, the precursor solution contains PVA-[PbI x ] 2-x Complex.
[0009] Preferably, the solid-to-liquid ratio of PVA to water in the PVA aqueous solution is (5-50) g:100 ml.
[0010] More preferably, the solid-to-liquid ratio of PVA to water in the PVA aqueous solution is (8-20) g:100 ml.
[0011] Preferably, the molar ratio of PbI2 to CsI is 1:(1-20).
[0012] More preferably, the molar ratio of PbI2 to CsI is 1:(1.1-10).
[0013] More preferably, the molar ratio of PbI2 to CsI is 1:(1.7-5).
[0014] Preferably, the PbI2 content in the precursor solution is 0.1-10.0 wt‰, and the CsI content is 1.0-20.0 wt‰.
[0015] More preferably, the PbI2 content in the precursor solution is 0.1-3.0 wt‰, and the CsI content is 3.0-10.0 wt‰.
[0016] Preferably, the ultrasound includes one or both of ultrasonic cell crusher ultrasonic dispersion and constant temperature ultrasound; the ultrasound temperature is 0 to 15° C. and the time is 1 to 1000 min.
[0017] More preferably, the ultrasonic cell pulverizer uses an ultrasonic dispersion process at a temperature of 0 to 15° C. for a time of 1 to 100 min.
[0018] More preferably, the temperature in the constant temperature ultrasound is 0-10° C., and the time is 10-600 min.
[0019] Preferably, the water-based efficient and stable CsPbI3 quantum dot optical film is prepared by adding CsI and PbI2 to a PVA aqueous solution, stirring in an ice-water bath to obtain a precursor solution, and the precursor solution is sequentially dispersed by an ultrasonic cell crusher, subjected to constant temperature ultrasound, scraped, heated to form a film, and subjected to humidity treatment.
[0020] Preferably, the temperature during the heating film forming is 50-100° C. and the time is 0.1-30 min.
[0021] More preferably, the temperature during the heating film forming is 50 to 70° C. and the time is 1 to 10 minutes.
[0022] More preferably, the temperature during the heating film forming is 50-60° C. and the time is 2-8 min.
[0023] Preferably, the temperature during the humidity treatment is 10-40° C., the relative humidity is 30-70%, and the placement time is 1-60 min.
[0024] More preferably, the temperature during the humidity treatment is 20-40° C., the relative humidity is 40-60%, and the placement time is 5-40 min.
[0025] More preferably, the temperature during the humidity treatment is 35° C., the relative humidity is 50%, and the placement time is 10 to 35 minutes.
[0026] Preferably, the photoluminescence quantum yield of the aqueous-based efficient and stable CsPbI3 quantum dot optical film is ≥60%.
[0027] Further preferably, the photoluminescence quantum yield of the water-based efficient and stable CsPbI3 quantum dot optical film is ≥80%.
[0028] More preferably, the photoluminescence quantum yield of the aqueous-based efficient and stable CsPbI3 quantum dot optical film is greater than 90%.
[0029] Preferably, after the aqueous-based high-efficiency and stable CsPbI3 quantum dot optical film is aged at 80°C for 1000 hours, the luminescence intensity is ≥ 90% of the initial luminescence intensity.
[0030] Further preferably, after the aqueous-based high-efficiency and stable CsPbI3 quantum dot optical film is aged at 80°C for 1000 hours, the luminescence intensity is ≥ 97% of the initial luminescence intensity.
[0031] As a preferred method, the aqueous-based CsPbI3 quantum dot optical film is highly efficient and stable at 13 mW cm -2, after aging for 1000h under 460nm blue light, the luminous intensity is ≥90% of the initial luminous intensity.
[0032] Further optimization, the water-based efficient and stable CsPbI3 quantum dot optical film has a thermal conductivity of 13 mW cm -2 After aging for 1000h under 460nm blue light, the luminous intensity is ≥97% of the initial luminous intensity.
[0033] A low-temperature preparation method for a water-based, efficient and stable CsPbI3 quantum dot optical film comprises: adding CsI and PbI2 into a PVA aqueous solution to obtain a precursor solution, and sequentially subjecting the precursor solution to ultrasonic treatment, scraping, heating film formation and humidity treatment.
[0034] Preferably, the ultrasound includes one or both of ultrasonic cell crusher ultrasonic dispersion and constant temperature ultrasound; the ultrasound temperature is 0 to 15° C. and the time is 1 to 1000 min.
[0035] More preferably, the ultrasonic cell pulverizer uses an ultrasonic dispersion process at a temperature of 0 to 15° C. for a time of 1 to 100 min.
[0036] More preferably, the temperature in the constant temperature ultrasound is 0-10° C., and the time is 10-600 min.
[0037] Preferably, the low-temperature preparation method of the aqueous-based efficient and stable CsPbI3 quantum dot optical film comprises:
[0038] S1. Add PbI2 and CsI to the PVA aqueous solution and stir in an ice-water bath to obtain a precursor solution;
[0039] S2, ultrasonically dispersing the precursor solution at 0-15°C using an ultrasonic cell crusher, and ultrasonically dispersing the precursor solution at a constant temperature of 0-10°C to obtain a transparent yellow solution;
[0040] S3, dropping the transparent yellow solution onto the surface of the flat glass, scraping to obtain a liquid precursor layer, and then heating at 50-100° C. to form a film to obtain a thin film;
[0041] S4. Place the flat glass with the film in an environment with a temperature of 10-40° C. and a relative humidity of 30-70% to obtain a water-based, highly efficient and stable CsPbI3 quantum dot optical film that emits red light.
[0042] Preferably, in S1, PVA is added to water, heated to dissolve, and then cooled to room temperature to obtain a PVA aqueous solution.
[0043] Preferably, the solid-to-liquid ratio of PVA to water in the PVA aqueous solution in S1 is (5-50) g:100 ml.
[0044] More preferably, the solid-to-liquid ratio of PVA to water in the PVA aqueous solution is (8-20) g:100 ml.
[0045] Preferably, the molar ratio of PbI2 to CsI in S1 is 1:(1-20).
[0046] More preferably, the molar ratio of PbI2 to CsI is 1:(1.1-10).
[0047] More preferably, the molar ratio of PbI2 to CsI is 1:(1.7-5).
[0048] Preferably, the PbI2 content in the precursor solution in S1 is 0.1-10.0 wt‰, and the CsI content is 1.0-20.0 wt‰.
[0049] More preferably, the PbI2 content in the precursor solution is 0.1-3.0 wt‰, and the CsI content is 3.0-10.0 wt‰.
[0050] Preferably, the precursor solution in S1 contains PVA-[PbI x ] 2-x Complex.
[0051] Preferably, the temperature of the heating film forming in S3 is 50-100° C. and the time is 0.1-30 min.
[0052] More preferably, the temperature during the heating film forming is 50 to 70° C. and the time is 1 to 10 minutes.
[0053] Preferably, in the humidity treatment in S4, the temperature is 10-40° C., the relative humidity is 30-70%, and the standing time is 1-60 min.
[0054] More preferably, the temperature during the humidity treatment is 20-40° C., the relative humidity is 40-60%, and the placement time is 5-40 min.
[0055] Preferably, the low-temperature preparation method of the aqueous-based efficient and stable CsPbI3 quantum dot optical film comprises:
[0056] S1. Add PbI2 and CsI to the PVA aqueous solution and stir in an ice-water bath to obtain a precursor solution;
[0057] S2, ultrasonically dispersing the precursor solution at 0-15°C with an ultrasonic cell crusher for 1-100 min; then ultrasonically dispersing at a constant temperature of 0-10°C for 10-600 min to obtain a transparent yellow solution;
[0058] S3, dropping the transparent yellow solution onto the surface of the flat glass, scraping to obtain a liquid precursor layer, and then heating at 50-100° C. to form a film to obtain a thin film;
[0059] S4. Place the flat glass with the film in an environment with a temperature of 10-40° C. and a relative humidity of 30-70% to obtain a water-based, highly efficient and stable CsPbI3 quantum dot optical film that emits red light.
[0060] Compared with the prior art, the present invention has the following beneficial effects:
[0061] 1. The present invention utilizes the interaction between polymer and perovskite in an aqueous solvent system to synthesize CsPbI3@PVA under low temperature conditions, and avoids the transition of the generated luminescent phase CsPbI3 to a non-luminescent yellow phase under the support bonding of the polymer.
[0062] 2. The present invention increases the viscosity of the precursor solution (the concentration of the PVA aqueous solution) so that the PbI2, which is originally slightly soluble in the water solvent, is dispersed in the system in the form of tiny particles to form a uniform and stable suspension, and the hydroxyl groups of the polymer PVA react with PbI2 to form PVA-[PbI x ] 2-x complex to achieve uniform dispersion of PbI2.
[0063] 3. The present invention forms a chemical bond between the polymer PVA and the perovskite precursor / perovskite, which significantly reduces the energy barrier that needs to be overcome for the film-forming reaction, thereby significantly reducing the heating temperature required for the film-forming reaction. Compared with the existing higher film-forming temperature, the film-forming temperature of the present invention can be as low as 50°C, which saves energy and reduces the difficult operation and danger that may be encountered in the high-temperature preparation process.
[0064] 4. In the present invention, the preparation process after PbI2 and CsI are added to the PVA aqueous solution and before coating and heating to form a film is kept at a low temperature to avoid excessive hydrolysis of PbI2 due to excessive temperature, which causes the prepared film to turn white and thus affects its luminescence performance.
[0065] 5. The present invention controls the water absorption temperature and relative humidity of air during humidity treatment to ensure that the water absorption process proceeds slowly, effectively preventing the occurrence of the coffee ring effect and increasing the uniformity of the film.
[0066] 6. The water-based, highly efficient and stable CsPbI3 quantum dot optical film prepared by the present invention has good photoluminescence efficiency, thermal stability and anti-blue light stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0067] Figure 1 This is a transmission electron microscope (TEM) image of the water-based, highly efficient and stable CsPbI3 quantum dot optical film prepared in Example 1 of the present invention.
[0068] Figure 2 This is the XRD diffraction pattern of the water-based high-efficiency and stable CsPbI3 quantum dot optical film and the polymer matrix PVA prepared in Example 1 of the present invention.
[0069] Figure 3 These are digital photos of water-based, highly efficient and stable CsPbI3 quantum dot optical films prepared under different heating film forming temperature conditions in Examples 1 and 8 to 15 of the present invention.
[0070] Figure 4 The photoluminescence spectra of water-based, highly efficient and stable CsPbI3 quantum dot optical films prepared under different film-forming temperature conditions in Examples 1 and 8 to 15 of the present invention are shown.
[0071] Figure 5 The half-peak width and luminescence peak position corresponding to the photoluminescence spectrum of the water-based high-efficiency and stable CsPbI3 quantum dot optical film prepared under different heating film forming temperature conditions in Examples 1 and 8 to 15 of the present invention.
[0072] Figure 6 The photoluminescence spectra of water-based highly efficient and stable CsPbI3 quantum dot optical films prepared under humidity treatment conditions of different placement times in Examples 1 and 16 to 25 of the present invention are shown.
[0073] Figure 7 These are digital photos of the water-based, highly efficient and stable CsPbI3 quantum dot optical films prepared under humidity treatment conditions for different placement times in Examples 1 and 16 to 25 of the present invention, as well as the corresponding relative intensities and half-peak widths.
[0074] Figure 8 This is a 2D photoluminescence spectrum of the water-based, efficient and stable CsPbI3 quantum dot optical film prepared in Example 1 of the present invention aged for 0 to 1000 hours under heating conditions at 80°C.
[0075] Fig. 9 The water-based, highly efficient and stable CsPbI3 quantum dot optical film prepared in Example 1 of the present invention has an output power of 13 mW cm -2 , 2D photoluminescence spectrum of aging from 0 to 1000h under 460nm blue light irradiation. DETAILED DESCRIPTION
[0076] The following are specific embodiments of the present invention, which further describe the technical solutions of the present invention, but the present invention is not limited to these embodiments.
[0077] Unless otherwise specified, the materials used in the present invention are conventional commercial products, and the methods used are conventional technical means.
[0078] The preparation method of the water-based efficient and stable CsPbI3 quantum dot optical film of the present invention comprises:
[0079] S1. PVA is added to water, heated to dissolve, and then cooled to room temperature to obtain a PVA aqueous solution. PbI2 and CsI are added to the aforementioned PVA aqueous solution, and stirred in an ice-water bath for 1 to 48 hours to obtain a precursor solution.
[0080] The solid-liquid ratio of the PVA and water is (5-50) g:100 ml;
[0081] The molar ratio of PbI2 to CsI is 1:(1-20);
[0082] The precursor solution contains PVA-[PbI x ] 2-x Complexes;
[0083] S2, ultrasonically dispersing the precursor solution at 0-15°C with an ultrasonic cell crusher for 1-100 min; then ultrasonically dispersing at a constant temperature of 0-10°C for 10-600 min to obtain a transparent yellow solution;
[0084] The transparent yellow solution contains PVA-[PbI x ] 2-x Complexes;
[0085] S3. Drop the transparent yellow solution onto the surface of the flat glass, scrape and apply it to obtain a liquid precursor layer, and then heat it at 50-100° C. for 1-60 min to obtain a thin film.
[0086] S4. Place the flat glass with the film in an environment with a temperature of 10-40° C. and a relative humidity of 30-70% for 1-60 minutes to obtain a water-based, highly efficient and stable CsPbI3 quantum dot optical film that emits red light.
[0087] In this article, the PVA aqueous solution is prepared by all methods that can achieve miscibility between PVA and water.
[0088] Herein, the liquid precursor layer is obtained by knife coating according to a method known to those skilled in the art.
[0089] The water-based, highly efficient and stable CsPbI3 quantum dot optical film of the present invention exhibits a photoluminescence quantum yield of ≥60% at 686 nm.
[0090] The water-based high-efficiency and stable CsPbI3 quantum dot optical film of the present invention has a luminous intensity of ≥ 90% of the initial luminous intensity after aging at 80°C for 1000h; -2 , after aging for 1000h under 460nm blue light, the luminous intensity is ≥90% of the initial luminous intensity.
[0091] Example 1
[0092] S1. Add 10 g of PVA to 100 mL of deionized water, heat at 95 °C to dissolve for 5 h, and then cool to room temperature to obtain a PVA aqueous solution. Add 230 mg of PbI2 and 467 mg of CsI to the aforementioned PVA aqueous solution, and stir in an ice-water bath for 12 h to obtain a precursor solution.
[0093] S2. The precursor solution was placed in an ultrasonic cell disruptor for accelerated dispersion at 5°C for 10 minutes, and then placed in an ultrasonic machine for constant temperature ultrasound at 5°C for 100 minutes to obtain a transparent yellow solution.
[0094] S3. Drop the transparent yellow solution onto the surface of the flat glass, obtain a liquid precursor layer by scraping, and then heat at 50° C. for 5 minutes to form a film to obtain a thin film.
[0095] S4. Place the flat glass with the film in an environment with a temperature of 35° C. and a relative humidity of 50% for 20 minutes to obtain a water-based, efficient and stable CsPbI3 quantum dot optical film with red light emission.
[0096] The photoluminescence quantum yield of the water-based, efficient and stable CsPbI3 quantum dot optical film is 91%.
[0097] Embodiments 2 to 4
[0098] S1. Add 8, 12, and 14 g of PVA to 100 mL of deionized water, respectively. Heat at 95 °C to dissolve for 5 h, then cool to room temperature to obtain a PVA aqueous solution. Add 230 mg of PbI2 and 467 mg of CsI to the aforementioned PVA aqueous solution, and stir in an ice-water bath for 12 h to obtain a precursor solution.
[0099] S2. The precursor solution was placed in an ultrasonic cell disruptor for accelerated dispersion at 5°C for 10 minutes, and then placed in an ultrasonic machine for constant temperature ultrasound at 5°C for 100 minutes to obtain a transparent yellow solution.
[0100] S3. Drop the transparent yellow solution onto the surface of the flat glass, obtain a liquid precursor layer by scraping, and then heat at 50° C. for 5 minutes to form a film to obtain a thin film.
[0101] S4. Place the flat glass with the film in an environment with a temperature of 35° C. and a relative humidity of 50% for 20 minutes to obtain a water-based, highly efficient and stable CsPbI3 quantum dot optical film that emits red light.
[0102] The photoluminescence quantum yields of the water-based, efficient and stable CsPbI3 quantum dot optical films are 70%, 76% and 83% respectively.
[0103] Embodiments 5 to 7
[0104] S1. Add 10 g of PVA to 100 mL of deionized water, heat at 95 °C to dissolve for 5 h, and then cool to room temperature to obtain a PVA aqueous solution. Add 230 mg of PbI2 and 467 mg of CsI to the aforementioned PVA aqueous solution, and stir in an ice-water bath for 12 h to obtain a precursor solution.
[0105] S2. The precursor solution was placed in an ultrasonic cell pulverizer for accelerated dispersion at 0, 10, and 15°C for 10 min, and then placed in an ultrasonic machine for constant temperature ultrasound at 5°C for 100 min to obtain a transparent yellow solution.
[0106] S3. Drop the transparent yellow solution onto the surface of the flat glass, obtain a liquid precursor layer by scraping, and then heat at 50° C. for 5 minutes to form a film to obtain a thin film.
[0107] S4. Place the flat glass with the film in an environment with a temperature of 35° C. and a relative humidity of 50% for 20 minutes to obtain a water-based, highly efficient and stable CsPbI3 quantum dot optical film that emits red light.
[0108] The photoluminescence quantum yields of the water-based, efficient and stable CsPbI3 quantum dot optical films are 72%, 71% and 65% respectively.
[0109] Embodiments 8 to 15
[0110] S1. Add 10 g of PVA to 100 mL of deionized water, heat at 95 °C to dissolve for 5 h, and then cool to room temperature to obtain a PVA aqueous solution. Add 230 mg of PbI2 and 467 mg of CsI to the aforementioned PVA aqueous solution, and stir in an ice-water bath for 12 h to obtain a precursor solution.
[0111] S2. The precursor solution was placed in an ultrasonic cell disruptor for accelerated dispersion at 5°C for 10 minutes, and then placed in an ultrasonic machine for constant temperature ultrasound at 5°C for 100 minutes to obtain a transparent yellow solution.
[0112] S3. Drop the transparent yellow solution onto the surface of the flat glass, obtain a liquid precursor layer by scraping, and then heat it at 40, 60, 70, 80, 90, 100, 110, and 120° C. to form a film.
[0113] S4. Place the flat glass with the film in an environment with a temperature of 35° C. and a relative humidity of 50% for 20 minutes to obtain a water-based, highly efficient and stable CsPbI3 quantum dot optical film that emits red light.
[0114] The photoluminescence quantum yields of the water-based efficient and stable CsPbI3 quantum dot optical films are 0%, 65%, 52%, 45%, 20%, 10%, 1.1%, and 0.9%, respectively.
[0115] Embodiments 16 to 25
[0116] S1. Add 10 g of PVA to 100 mL of deionized water, heat at 95 °C to dissolve for 5 h, and then cool to room temperature to obtain a PVA aqueous solution. Add 230 mg of PbI2 and 467 mg of CsI to the aforementioned PVA aqueous solution, and stir in an ice-water bath for 12 h to obtain a precursor solution.
[0117] S2. The precursor solution was placed in an ultrasonic cell disruptor for accelerated dispersion at 5°C for 10 minutes, and then placed in an ultrasonic machine for constant temperature ultrasound at 5°C for 100 minutes to obtain a transparent yellow solution.
[0118] S3. Drop the transparent yellow solution onto the surface of the flat glass, obtain a liquid precursor layer by scraping, and then heat at 50° C. for 5 minutes to form a film to obtain a thin film.
[0119] S4. Place the flat glass with the film in an environment with a temperature of 35°C and a relative humidity of 50% for 5, 10, 15, 25, 30, 35, 40, 45, 50, and 55 minutes respectively to obtain a water-based, efficient, and stable CsPbI3 quantum dot optical film with red light emission.
[0120] The photoluminescence quantum yields of the water-based high-efficiency and stable CsPbI3 quantum dot optical films are 0%, 62%, 80%, 78%, 65%, 60%, 45%, 30%, 10%, 10%, and 10%, respectively.
[0121] Embodiment 26
[0122] S1. Add 20 g of PVA to 100 mL of deionized water, heat at 95 °C to dissolve for 5 h, and then cool to room temperature to obtain a PVA aqueous solution. Add 230 mg of PbI2 and 467 mg of CsI to the aforementioned PVA aqueous solution, and stir in an ice-water bath for 12 h to obtain a precursor solution.
[0123] S2. The precursor solution was placed in an ultrasonic cell disruptor for accelerated dispersion at 5°C for 10 minutes, and then placed in an ultrasonic machine for constant temperature ultrasound at 5°C for 100 minutes to obtain a transparent yellow solution.
[0124] S3. Drop the transparent yellow solution onto the surface of the flat glass, obtain a liquid precursor layer by scraping, and then heat at 50° C. for 5 minutes to form a film to obtain a thin film.
[0125] S4. Place the flat glass with the film in an environment with a temperature of 35° C. and a relative humidity of 50% for 20 minutes to obtain a water-based, highly efficient and stable CsPbI3 quantum dot optical film that emits red light.
[0126] The photoluminescence quantum yield of the aqueous-based, highly efficient and stable CsPbI3 quantum dot optical film is 45%.
[0127] Embodiment 27
[0128] S1. Add 10 g of PVA to 100 mL of deionized water, heat at 95 °C to dissolve for 5 h, and then cool to room temperature to obtain a PVA aqueous solution. Add 461 mg of PbI2 and 260 mg of CsI to the aforementioned PVA aqueous solution, and stir in an ice-water bath for 12 h to obtain a precursor solution.
[0129] S2. The precursor solution was placed in an ultrasonic cell disruptor for accelerated dispersion at 5°C for 10 minutes, and then placed in an ultrasonic machine for constant temperature ultrasound at 5°C for 100 minutes to obtain a transparent yellow solution.
[0130] S3. Drop the transparent yellow solution onto the surface of the flat glass, obtain a liquid precursor layer by scraping, and then heat at 50° C. for 5 minutes to form a film to obtain a thin film.
[0131] S4. Place the flat glass with the film in an environment with a temperature of 35° C. and a relative humidity of 50% for 20 minutes to obtain a water-based, highly efficient and stable CsPbI3 quantum dot optical film that emits red light.
[0132] The photoluminescence quantum yield of the aqueous-based, highly efficient and stable CsPbI3 quantum dot optical film is 20%.
[0133] Embodiment 28
[0134] S1. Add 10 g of PVA to 100 mL of deionized water, heat at 95 °C to dissolve for 5 h, and then cool to room temperature to obtain a PVA aqueous solution. Add 830 mg of PbI2 and 130 mg of CsI to the aforementioned PVA aqueous solution, and stir in an ice-water bath for 12 h to obtain a precursor solution.
[0135] S2. The precursor solution was placed in an ultrasonic cell disruptor for accelerated dispersion at 5°C for 10 minutes, and then placed in an ultrasonic machine for constant temperature ultrasound at 5°C for 100 minutes to obtain a transparent yellow solution.
[0136] S3. Drop the transparent yellow solution onto the surface of a flat glass, obtain a liquid precursor layer by scraping, and then heat and dry at 50° C. for 5 min to obtain a thin film.
[0137] S4. The flat glass with the film is placed in an environment with a temperature of 35° C. and a relative humidity of 50% for 20 minutes. The photoluminescence quantum yield of the obtained CsPbI3 film is 20%.
[0138] Figure 1This is a transmission electron microscopy (TEM) image of the water-based, efficient and stable CsPbI3 quantum dot optical film prepared in Example 1. The black particles in the image are CsPbI3 quantum dots, with an average diameter of about 24.5 nm and a relatively uniform size distribution.
[0139] Figure 2 The XRD diffraction patterns of the water-based efficient and stable CsPbI3 quantum dot optical film and the polymer matrix PVA successfully prepared in Example 1 are shown in detail. Through comparative analysis, it is found that the diffraction pattern of the prepared water-based efficient and stable CsPbI3 quantum dot optical film is highly consistent with the data on the standard card, which fully proves that CsPbI3 quantum dots have indeed been successfully grown inside the polymer matrix.
[0140] Figure 3 , 4 , 5 are digital photos, photoluminescence spectra, corresponding half-peak widths and luminescence peak positions of water-based efficient and stable CsPbI3 quantum dot optical films prepared under different heating film-forming temperature conditions in Example 1 and Examples 8 to 15, respectively. It can be seen that increasing the heating film-forming temperature (from 50°C to 100°C) will cause the PL peak to gradually blue-shift from 686nm to 606nm, and the half-peak full-width value will increase. This broadening is mainly attributed to the accelerated curing speed of the matrix material, which limits the size of the internal core and hinders its subsequent growth. During the extended heating process at a low temperature of 50°C, the solvent evaporation rate is slow, allowing the precursor to react more fully to form a non-luminescent intermediate. In addition, the present invention controls the heating film-forming temperature, relative humidity and other parameters to achieve a suitable solvent evaporation rate and the subsequent slow water absorption process, which effectively prevents the occurrence of the coffee ring effect and increases the uniformity of the film.
[0141] In Example 8, the film was formed by heating at a temperature below 50°C, and the energy provided was insufficient to form a stable luminescent phase CsPbI3. In Examples 14 and 15, the film was formed by heating at a temperature above 100°C, and the matrix material hardened excessively and quickly absorbed moisture, resulting in rapid decomposition of the synthesized luminescent phase perovskite.
[0142] Figure 5 , 6The photoluminescence spectra of water-based efficient and stable CsPbI3 quantum dot optical films prepared under different humidity treatment conditions for different placement times in Examples 1 and 16 to 25 and the corresponding relative intensity and half-peak width are shown. The results reveal the process of water-induced nucleation, growth and final decomposition of CsPbI3 in the composite film prepared under water absorption conditions at 35°C and 50% relative humidity (RH). Initially, with the nucleation and growth of the internal nucleus, the photoluminescence intensity of the water-based efficient and stable CsPbI3 quantum dot optical film increases with time; then, continuous water absorption causes the already generated luminescent phase CsPbI3 to dissolve or transform into a non-luminescent yellow phase, resulting in a gradual decrease in the photoluminescence intensity of the water-based efficient and stable CsPbI3 quantum dot optical film. The continuous red shift of the luminescence wavelength of the water-based efficient and stable CsPbI3 quantum dot optical film during the entire water absorption process corresponds to the increase in the grain size of the luminescent phase CsPbI3. After 20 minutes of humidity treatment, the water-based high-efficiency and stable CsPbI3 quantum dot optical film achieved the best photoluminescence performance, showing a photoluminescence quantum yield of 91% at 686nm.
[0143] Figure 8 , 9 The water-based, highly efficient and stable CsPbI3 quantum dot optical film prepared in Example 1 was heated at 80°C and 13 mW cm -2 , 2D photoluminescence spectrum under 460nm blue light irradiation. Heating at 80℃ and 13mW cm -2 After aging with 460nm blue light for 1000 hours, the wavelength and other optical parameters of the water-based efficient and stable CsPbI3 quantum dot optical film remain basically unchanged, proving that the water-based efficient and stable CsPbI3 quantum dot optical film of the present invention has good stability.
[0144] In summary, the present invention utilizes the interaction between polymer and perovskite in an aqueous solvent system to synthesize CsPbI3@PVA under low temperature conditions, and avoids the transition of the generated luminescent phase CsPbI3 to a non-luminescent yellow phase under the support and bonding of the polymer; the obtained aqueous-based high-efficiency and stable CsPbI3 quantum dot optical film has good photoluminescence quantum yield and luminescence intensity stability.
[0145] The specific embodiments described herein are merely examples of the spirit of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in similar ways, but they will not deviate from the spirit of the present invention or exceed the scope defined by the appended claims.
Claims
1. A water-based, efficient and stable CsPbI3 quantum dot optical film, characterized in that: The method is prepared by adding CsI and PbI2 into a PVA aqueous solution to obtain a precursor solution, and the precursor solution is subjected to ultrasound, scraping, heating film formation, and humidity treatment.
2. The water-based, efficient and stable CsPbI3 quantum dot optical film according to claim 1, characterized in that: The precursor solution contains PVA-[PbI x ] 2-x Complex.
3. The water-based, efficient and stable CsPbI3 quantum dot optical film according to claim 1, characterized in that: The solid-to-liquid ratio of PVA to water in the PVA aqueous solution is (5-50) g:100 ml.
4. The water-based, efficient and stable CsPbI3 quantum dot optical film according to claim 1, characterized in that: The molar ratio of PbI2 to CsI is 1:(1-20).
5. The water-based, efficient and stable CsPbI3 quantum dot optical film according to claim 1, characterized in that: The ultrasound includes one or both of ultrasonic cell crusher ultrasonic dispersion and constant temperature ultrasound; the ultrasound temperature is 0-15°C and the time is 1-1000min.
6. The water-based, efficient and stable CsPbI3 quantum dot optical film according to claim 1, characterized in that: The temperature during the heating film forming is 50-100° C. and the time is 0.1-30 min.
7. The water-based, efficient and stable CsPbI3 quantum dot optical film according to claim 1, characterized in that: The temperature during the humidity treatment is 10-40° C., the relative humidity is 30-70%, and the placement time is 1-60 minutes.
8. The water-based, efficient and stable CsPbI3 quantum dot optical film according to claim 1, characterized in that: The water-based efficient and stable CsPbI3 quantum dot optical film is prepared by adding CsI and PbI2 into a PVA aqueous solution, stirring in an ice-water bath to obtain a precursor solution, and the precursor solution is sequentially dispersed by an ultrasonic cell crusher, subjected to constant temperature ultrasound, scraped, heated to form a film, and subjected to humidity treatment.
9. A low-temperature preparation method for a water-based, efficient and stable CsPbI3 quantum dot optical film, characterized in that: The preparation method comprises: adding CsI and PbI2 into a PVA aqueous solution to obtain a precursor solution, and sequentially subjecting the precursor solution to ultrasonic treatment, scraping, heating to form a film, and humidity treatment.
10. The low-temperature preparation method of the aqueous-based, efficient and stable CsPbI3 quantum dot optical film according to claim 9, characterized in that: include: S1. Add PbI2 and CsI to the PVA aqueous solution and stir in an ice-water bath to obtain a precursor solution; S2, subjecting the precursor solution to ultrasonic dispersion and constant temperature ultrasonication using an ultrasonic cell crusher to obtain a transparent yellow solution; S3, drop the transparent yellow solution onto the surface of the flat glass, scrape and apply to obtain a liquid precursor layer, and then heat at 50-100° C. to form a film to obtain a thin film; S4. Place the flat glass with the film in an environment with a temperature of 10-40° C. and a relative humidity of 30-70% to obtain a water-based, highly efficient and stable CsPbI3 quantum dot optical film that emits red light.